1998
DOI: 10.1073/pnas.95.23.13681
|View full text |Cite
|
Sign up to set email alerts
|

Specific interaction of mutant p53 with regions of matrix attachment region DNA elements (MARs) with a high potential for base-unpairing

Abstract: Mutant, but not wild-type p53 binds with high affinity to a variety of MAR-DNA elements (MARs), suggesting that MAR-binding of mutant p53 relates to the dominantoncogenic activities proposed for mutant p53. MARs recognized by mutant p53 share AT richness and contain variations of an AATATATTT ''DNA-unwinding motif,'' which enhances the structural dynamics of chromatin and promotes regional DNA base-unpairing. Mutant p53 specifically interacted with MARderived oligonucleotides carrying such unwinding motifs, ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
38
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…In summary, the CHIP-DNA fragments identi®ed as possible in vivo targets for mutant p53 in Onda 11 cells did not show any common sequence homology, rendering it extremely unlikely that their speci®c binding by mut p53 (Ser 245 ) is mediated by a common sequence element. In line with our previous analyses of the binding of mut p53 to MARs (Weissker et al, 1992;Muller et al, 1996;Will et al, 1998b), we therefore propose that structural determinants, speci®cally the ability of these DNAs to adopt a certain non-B-DNA conformation(s) determines their binding to mut p53.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…In summary, the CHIP-DNA fragments identi®ed as possible in vivo targets for mutant p53 in Onda 11 cells did not show any common sequence homology, rendering it extremely unlikely that their speci®c binding by mut p53 (Ser 245 ) is mediated by a common sequence element. In line with our previous analyses of the binding of mut p53 to MARs (Weissker et al, 1992;Muller et al, 1996;Will et al, 1998b), we therefore propose that structural determinants, speci®cally the ability of these DNAs to adopt a certain non-B-DNA conformation(s) determines their binding to mut p53.…”
supporting
confidence: 88%
“…Photographs were taken with a Leica DMRA¯uorescence microscope (Leica) equipped with a CCD camera SPOT (DIAGNOSTIC instruments inc.). Note that the cytoplasmic staining of the p53 protein and the reduction of nuclear p53 staining are observed only in cells which had been injected with plasmids containing cloned CHIP-DNA fragments, but not in cells which had been injected with control plasmid elements promoting the formation of non-B-DNA structures (Will et al, 1998b). However, as we so far did not ®nd any known promoter sequence adjacent to (CA)n repeats in our CHIP-DNA fragments, the functional relevance of the interaction of mut p53 with (CA)n repeats in Onda 11 cells awaits further clari®cation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it is possible that the nonSSDB activity of the p53 C terminus is also regulating the specificity of mutp53 DNA binding. This idea is supported by the finding that mutp53 DNA binding requires the same domains involved in wtp53-SSDB to non-linear DNA, namely the core domain and the C terminus (Muller et al, 1996;Will et al, 1998), as well as by the finding that these domains were necessary for the transactivation of some promoters by mutp53 (Frazier et al, 1998;Lanyi et al, 1998) and for some of mutp53 oncogenic functions . Further support for this notion is offered by studies showing that post-translational alterations of the C terminus affects mutp53 transcriptional activities (Yap et al, 2004;Di Agostino et al, 2006).…”
Section: Mutp53: Role Of Residual Wtp53 Activity?mentioning
confidence: 93%
“…At this regard, it has been demonstrated that mutant p53 binds to its family members, p63 and p73, impairing their transcriptional activity and consequently their antitumoral effects. [19][20][21][22] (iii) Mutant p53 protein, for which the attempts to delineate a specific DNA-binding sequence distinct from those regulated by wt p53 have failed, has been reported to directly bind a wide range of DNA secondary structures, such as matrix attachment regions with a high potential of base unpairing in vitro, 23 or non-B DNA structures. 24 This might imply that chromatin remodeling may be involved in transcriptional activities mediated by mutant p53 protein.…”
mentioning
confidence: 99%